Protective Factors for Sexual Violence: Understanding How Trajectories Relate to Perpetration in High School - Basile, Kathleen C. (Prev Sci, 2018)
Adolescent sexual violence (SV) perpetration is a significant public health problem. Many risk factors for perpetration are known, but less is known about what protects youth from perpetration, or how protective factors change over time. This longitudinal study reports trajectories of four potential protective factors for SV perpetration (empathy, parental monitoring, social support, and school belonging) across middle and high school and examines their relationship to SV perpetration in high school. Findings reveal that youth who identified as SV perpetrators had significantly lower mean empathy scores (d = − 0.18, 95 % CI [−0.26, −0.10]) and social support scores (d = − 0.05, 95 % CI [−0.14, −0.03]) at the beginning of middle school than non-perpetrators. We also found that youth who identified as SV perpetrators had a quicker deceleration in parental monitoring (slopes) and empathy from middle to high school, compared to non-perpetrators. Within-sex differences emerged; significant differences in slopes were detected for school belonging between male perpetrators and male non-perpetrators (Wald test = 3.76 (1), p = .05) and between female perpetrators and female non-perpetrators (Wald test = 3.95(1), p = .04). Significant differences in slopes for empathy between female perpetrators and female non-perpetrators (Wald test = 4.76(1), p = .03) were also detected. No differences were found between male and female SV perpetrators for either empathy or school belonging. These findings have implications for the content and timing of adolescent SV prevention efforts. Intervention in adolescence, involving parents and schools in a comprehensive, multi-level approach, may be effective in preventing SV perpetration.